An Untrodden Path: Versatile Fabrication of Self‐Supporting Polymer‐Stabilized Percolation Membranes (PSPMs) for Gas Separation. Issue 27 (13th April 2017) - Friebe, Sebastian; Mundstock, Alexander; Schneider, Daniel; Caro, Jürgen
Abstract: The preparation and scalability of zeolite or metal organic framework (MOF) membranes remains a major challenge, and thus prevents the application of these materials in large‐scale gas separation. Additionally, several zeolite or MOF materials are quite difficult or nearly impossible to grow as defect‐free layers, and require expensive macroporous ceramic or polymer supports. Here, we present new self‐supporting zeolite and MOF composite membranes, called Polymer‐Stabilized Percolation Membranes (PSPMs), consisting of a pressed gas selective percolation network (in our case ZIF‐8, NaX and MIL‐140) and a gas‐impermeable infiltrated epoxy resin for cohesion. We demonstrate the performance of these PSPMs by separating binary mixtures of H2 /CO2 and H2 /CH4 . We report the brickwork‐like architecture featuring selective percolation pathways and the polymer as a stabilizer, compare the mechanical stability of said membranes with competing materials, and give an outlook on how economic these membranes may become. Abstract : A novel membrane architecture was developed by pressing porous powders into pellets followed by an infiltration with a gas impermeable polymer. After opening the percolation paths by polishing, the membranes were tested for H2 /CO2 and H2 /CH4 separation. In comparison to other state of the art membranes and the corresponding supported layers, these so called Polymer‐Stabilized Percolation Membranes (PSPMs) feature similar capabilities above and around the Robeson boundary.